THE INFLUENCE OF WORD OF MOUTH,PRODUCT DESIGN,WARRANTY WITH BRAND IMAGE AS MODERATING VARIABLES ON PURCHASE DECISION (SURVEY ON THE COMMUNITY TUPPERWARE USERS IN MEDAN AREA MATSUMM CITY II) - Dea Claudia Br.Hutahaean Hutahaean; Saskia Saskia; indra Syafi'i (LLDIKTI Wilayah 1 Sumatera Utara, 2021)
The author's purpose of conducting research is to determine the effect of Word Of Mouth on Purchase Decisions, to determine the effect of Product Design on Purchase Decisions, to determine the effect of Warranty on Purchase Decisions, to determine the effect of Word Of Mouth on Purchase Decisions moderated by Brand Image, to determine the effect of Design Products on Purchase Decisions moderated by Brand Image and to determine the effect of Warranty on Purchase Decisions moderated by Brand Image on the Tupperware User Community in the Medan Area, Matsum II City. The sample in this study was 100 Tupperware users in the Medan Area, Matsum II City. This study was collected through a questionnaire which was processed and analyzed using the MRA method of analysis. Then test the quality of the data used is the validity test using Significant and reliability test using Cronbach Alpha. To test the hypothesis in this study. Researchers used the t test, and F test and did a determination test. The results of this study indicate that there is a positive influence of word of mouth on purchasing decisions, there is a positive influence of product design variables on purchasing decisions, there is a positive influence of warranty variables on purchasing decisions, brand image does not moderate the relationship between word of mouth on decisions in the tupperware user community in Medan area, Kota Matsum II, brand image does not moderate the relationship between product design and decisions in the Tupperware user community in Medan Area, Kota Matsum II and brand image moderates the relationship between warranty and decision on the Tupperware user community in Medan Area, Kota Matsum II